A rising tide of access: what consequences for equitable learning in Ethiopia?. (2nd September 2020) - Iyer, Padmini; Rolleston, Caine; Rose, Pauline; Woldehanna, Tassew
ABSTRACT: Primary school enrolment in Ethiopia has more than doubled over the past two decades. In spite of this impressive achievement, and as in many low- and middle-income countries that have experienced rapid expansion, the Ethiopian education system is characterised by a 'learning crisis' in which many children are leaving school without basic numeracy and literacy skills. In this paper, we explore the relationship between low learning levels and the features of an education system characterised by a sudden increase in learners from disadvantaged backgrounds, including 'first generation learners', or students whose parents have never been to school. Using unique longitudinal school survey data, we examine whether first-generation learner status represents an additional layer of disadvantage in the Ethiopian education system; the relationship between first-generation learner status and learning outcomes; and the educational trajectories of first generational learners through primary school. Based on these findings, we consider the implications of a rising tide of access for Ethiopia as it seeks to provide equitable, quality education for all by 2030.